Cone-beam computed tomography study of tooth root and canal morphology of permanent molars in a Serbian population - Popović, Milica; Živanović, Suzana; Vučićević, Tamara; Grujović, Miona; Papić, Miloš (Vojnosanitetski pregled, 2021)
Background/Aim. For successful endodontic therapy, it is necessary to know root morphology. Therefore, the aim of our study was to analyze root canal morphology and root canal length of permanent molars in a Serbian population, using cone-beam computed tomography (CBCT). Methods. The study included a total of 305 maxillary molars, and 280 mandibular molars receiving cone-beam computed tomography examination and determined root numbers, canal morphology according to Vertucci classification, and canal lengths. Results were correlated with sex and tooth location in the jaw. Results. The mesiobuccal roots of first maxillary molars showed Vertucci type I in 45.7%, followed by type II in 29% of cases. For the second molar, Vertucci type I was found in 60.5% of cases in mesiobuccal canals. Palatal and distobuccal canals mostly presented Vertucci type I configuration. The mesial roots of mandibular molars had the highest frequency of two canals with Vertucci type IV as the most frequent for the first molar, and Vertucci type II for the second molar. Distal roots most commonly had one canal in both molars. Palatal canal length was the highest in maxillary first molars, with the mean value of 20.62 mm, while in second molars, the highest length value was for the mesiobuccal canal (20.09 mm). In both mandibular molars the mesial root canal was the longest one. Differences were found according to sex and tooth location in the jaw. Conclusion. Mesiobuccal roots of maxillary first molars had two canals; it was more frequently compared to second molars. Mesial roots of mandibular molars showed same frequency of two canals, and diversity in Vertucci types. Male patients tended to have higher complexity of root canal morphology compared to that of females. CBCT can improve understanding of the root canal morphology.
Keywords: tooth root; molar; cone-beam computed tomography; serbia